Modelagem matemática e implementação computacional no ATP de um sistema solar fotovoltaico conectado a rede de baixa tensão - Cunha, Guilherme Henrique Bernardes (2013)
The increased demand for energy, the possibility of reducing the supply of conventional fuels and growing concerns about the preservation of the environment have led to several researches and development of alternative energy sources which are clean, renewable and with minor environmental impact. Among the various alternative energy sources, PV solar has been considered an excellent option as it is free, abundant, clean and distributed through all places. Solar energy incident on Earth\'s surface is estimated at about ten thousand times the total energy consumed in the world. Even with all the advantages offered by the generation of energy through the use of photovoltaic panels, the initial cost of deployment is high and the efficiency of energy conversion is currently still low. Thus, it is essential to use techniques to extract the maximum power from these panels to increase the system operation efficiency. This work aims to present studies of a complete photovoltaic solar system, connected to low voltage power grid including the solar panel, a step-up voltage converter, its corresponding Maximum Power Point Tracking (MPPT) control, the voltage inverter with its control, the phase locked loop, and by means of an inductive coupling, the connection of the whole system to the grid. For modeling and simulations of the solar photovoltaic system, it was used the Alternative Transients Program - ATP. Initially it is presented simulation results with parts that comprises the PV array, and only at the end, it is performed a case study with the complete PV system developed in this work.